Seismic anisotropy of the upper crust around Mount Fuji, Japan. Issue 4 (22nd April 2015) - Araragi, Kohtaro R.; Savage, Martha K.; Ohminato, Takao; Aoki, Yosuke
Abstract We measure shear wave splitting and estimate stresses of Mount Fuji, Japan, to interpret anisotropic structure and its implication for geologic processes using local crustal earthquake seismograms from 2009 to 2012. The measured fast polarizations have preferred orientations at each station with mean values of delay times <0.15 s. We infer that the anisotropic structure is located at shallow depths (<4 km) from a lack of focal depth dependence of delay times. The fast polarization directions for stations within approximately 15 km of the summit of Mount Fuji show a radial pattern pointing toward the summit, while stations far from the summit exhibit fast polarization directions approximately parallel to the NW‐SE compressional regional stress field. We infer that the symmetrical seismic anisotropic structure around the summit and the fast directions parallel to the regional compression observed at distant stations from the summit reflect interactions of the gravitational stresses and regional tectonics. Assuming stress control only, the spatial pattern of anisotropy can be fit by the interaction of gravitational with regional stresses if the regional maximum horizontal stress is 1.02 times lithostatic pressure (51.9 MPa at a depth of 2.0 km). If structural anisotropy also contributes to the radial pattern, then the regional maximum horizontal stress magnitude is not constrained.